2007
DOI: 10.1017/s0029665107005678
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and prebiotics in infant nutrition

Abstract: The human colonic microflora has a central role in health and disease, being unique in its complexity and range of functions. As such, dietary modulation is important for improved gut health, especially during the highly-sensitive stage of infancy. Diet can affect the composition of the gut microflora through the availability of different substrates for bacterial fermentation. Differences in gut microflora composition and incidence of infection exist between breast-fed and formula-fed infants, with the former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 72 publications
(110 reference statements)
0
79
0
2
Order By: Relevance
“…The probiotic should survive the environmental conditions in their target site of action and proliferate in this location (Havenaar & Huis int'Veld, 1992). That is, they should be able to adhere to and colonise the epithelial cell lining to establish themselves in the colon (Guarner & Schaafsma, 1998;Parracho et al, 2007). The ability to adhere to the epithelium secures the strain from being easily flushed out by peristaltic movements (Gupta & Garg, 2009).…”
Section: Desirable Properties For a Probiotic Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…The probiotic should survive the environmental conditions in their target site of action and proliferate in this location (Havenaar & Huis int'Veld, 1992). That is, they should be able to adhere to and colonise the epithelial cell lining to establish themselves in the colon (Guarner & Schaafsma, 1998;Parracho et al, 2007). The ability to adhere to the epithelium secures the strain from being easily flushed out by peristaltic movements (Gupta & Garg, 2009).…”
Section: Desirable Properties For a Probiotic Strainmentioning
confidence: 99%
“…The organism should be able to survive, in particular, the harsh environmental conditions of the stomach and small intestine (e.g. gastric and bile acids, digestive enzymes) (Dunne et al, 2001;Parracho et al, 2007).…”
Section: Desirable Properties For a Probiotic Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, manufacturers of formula try to mimic the gastrointestinal flora in breastfed infants by adding probiotics and/or prebiotics such as GOS. Although the addition of probiotics is able to manipulate the infants' microflora towards the breast-fed infants' microflora [17,18] , this concept may be regarded as unphysiological since breast milk itself does not contain bacteria. Prebiotics are, therefore, the first choice.…”
Section: Applicationsmentioning
confidence: 99%
“…The important criteria which are used for selecting probiotic strains includes that the organism should be: nonpathogenic and non-toxic (Singh et al 2011); isolated from the same species as its intended host (Maurya et al 2014); able to survive during transit through the gastrointestinal tract by being acid and bile resistant (Khan and Naz 2013;Maurya et al 2014); able to adhere and colonize the intestinal epithelium which is an important property for successful immune modulation and competitive exclusion of pathogens (Kechagia et al 2013;Maurya et al 2014); able to stabilize the normal intestinal microflora (Parvez et al 2006); able to produce antimicrobial substances like the bacteriocins against the pathogens (Kral et al 2012); having a demonstrated beneficial effect on the host (Fontana et al 2013); durable enough to withstand the duress of commercial manufacturing, processing and distribution (Khan and Naz 2013); and also having good sensory characteristics by not providing unpleasant flavors or textures (Parracho et al 2007;Mitropoulou et al 2013). The essential criteria for the use of probiotics in humans has been listed in Table 2.…”
Section: Desirable Probiotic Characteristicsmentioning
confidence: 99%